Promoting success in integrated secondary education: Guidelines for monitoring students - Almeida, Marcilene Dias Bruno de; Lyra-Silva, Gene Maria Vieira; Guimarães, Vânia Cláudia; Sousa, Cinthya Oliveira (Seven Editora, 2024)
The research aimed to build a Pedagogical Form for Student Diagnosis and Monitoring, as well as to establish a profile of the graduating student and identify the aspects that contribute to the permanence and success of students in High School Integrated to Professional Education. The locus was the Uruaçu Campus of the Federal Institute of Education, Science and Technology of Goiás. It was based on a literature review on school failure and success and the application of questionnaires to the graduating students, parents, teachers, and technicians in 2017. The case study was adopted as a research strategy and the qualitative and quantitative procedures were adopted using the inductive approach. From there, the construction and application of the Pedagogical Form for Student Diagnosis and Monitoring took place, through a web system, in the incoming classes of 2018. The results of the data collection were organized, disseminated, and discussed in the Class Council meetings and used by the Student Pedagogical Support team for the monitoring of students and classes. DOI:https://doi.org/10.56238/sevened2024.007-061